Unmanned Aerial Vehicles as a Source of Information Security Threats of Wireless Network - Voitenko, Serhii; Druzhynin, Volodymyr; Martyniuk, Hanna; Meleshko, Tetiana (International Journal of Computing, 2022)
This work deals with the identification of threats to wireless networks when considering an attacker from unmanned aerial vehicles. An analysis of heterogeneous networks built on 4 G technology, as objects of UAV attack, is performed. It is determined that the main problem of protecting wireless systems is the lack of protection of radio communication channels and the vulnerability of the base and subscriber station equipment. A model of the UAV as an intruder in the information security of wireless networks is built. The classification of various types of UAVs by targets and weapons of attack, methods of use and the ability to violate the criteria of protection of the information and telecommunication system is presented. A threat model that assesses the level of risks and losses in different types of attacks performed by different types of UAVs is built. It is expedient to use the received models as the basic ones when building a model of threats to a certain corporate network of the organization, developing ways and security means, estimating and controlling 4 G network protection against UAV.